Quality of life (QoL) in patients with heart failure with preserved ejection fraction (HFpEF): a systematic review. (3rd October 2022) - Chen, J; Hunt, P; Khordoc, C; Hardy, E; Mitchell, C
Abstract: Introduction: Heart failure with preserved ejection fraction (HFpEF) is associated with significant clinical unmet need as mortality and morbidity rates are high despite current treatments. Patient-reported quality of life (QoL) is an important and clinically relevant endpoint in patients with HF so understanding the impact of HFpEF on QoL is essential. Purpose: The aim of this systematic review was to identify and summarize data on QoL in HFpEF. Methods: Systematic searches of Medline, Medline Epub Ahead of Print (In-Process & Other Non-Indexed Citations), Embase, and EBM Reviews were conducted in October 2021. Congress proceedings from the past 3 years and reference lists of included publications were also searched. Publications were screened against eligibility criteria by title/abstract and then by full text. Eligibility criteria included clinical studies of any design reporting baseline QoL in adults with HFpEF published from 2016 onwards. Results: The electronic database search identified 6, 403 articles on HFpEF. After screening, 35 full publications reporting HFpEF and QoL were included. Study designs included observational cohort (n=17), cross-sectional (n=3), and post-hoc analyses of interventional studies (n=15). Tools used to measure QoL included KCCQ (n=17), MLHFQ (n=12), EQ-5D-VAS (n=8), SF-12 (n=2), SF-36 (n=2), and EHFSQ-1 (n=1). Health-state utility values (HSUVs) were captured using EQ-5D in four studies. HSUVs in HFpEF ranged from 0.67–0.74, indicating a substantial QoL burden. Eleven studies using various instruments compared QoL in patients with HFpEF vs non-HFpEF (Table 1). Of these, five reported statistically significantly poorer QOL in HFpEF vs non-HFpEF, one reported statistically significantly poorer QOL in non-HFpEF vs HFpEF and five found no statistically significant difference between HF subtypes. Four studies compared QoL in men vs women with three reporting statistically significantly worse QoL in women. Three studies examined the impact of comorbidities, and all reported statistically significantly poorer QoL in patients with comorbid atrial fibrillation, diabetes, or metabolic syndrome. Two studies examined the effect of age; one reported that, vs elderly patients (age ≥85 years), younger patients (age ≤55 years) with HFpEF had statistically significantly worse QoL despite having fewer comorbidities; in contrast, the second study reported that younger patients (age ≤55 years) had statistically significantly better QoL than elderly patients (age ≥75 years). Two studies reported on hospitalizations, with one reporting no difference in QoL between patients who had previously been hospitalized and those who had not and the other reporting that readmission for HF correlated with QoL. Conclusions: QoL burden among HFpEF patients is substantial. QoL may be affected by age, comorbidities, gender, and prior hospitalization, and may be associated with poorer outcomes. QoL in HFpEF is generally poorer than in non-HFpEF. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AstraZeneca